REDD+ as an International Cooperation Strategy under the Global Climate Change Regime - Park, Mi Sun (Taylor and Francis, 2013)
Under the global climate negotiations, a REDD+ (Reducing Emissions from Deforestation and Forest Degradation, conservation of forest carbon stocks; sustainable management of forests, and enhancement of forest carbon stocks) regime is established by multi-stakeholders such as transnational organizations, states, and non-governmental organizations (NGOs). However, several developed countries have strategically exerted their leadership in forming and implementing a REDD+ regime in the international community. This paper attempts to investigate national REDD+ strategies of Norway, Germany, Australia, the US, and Japan which have contributed to forming a global REDD+ regime. REDD+ strategies and policies of the five countries were analyzed using three categories: pledge, type of support, and approach. These five countries have commonalities in that they pledged their commitment to establishing a REDD+ architecture through non-binding agreements such as the Copenhagen Accord and the REDD+ Partnership. Furthermore, they have been providing developing countries with financial and technical assistance through multilateral and bilateral schemes using their own international initiatives on climate and forest. Nevertheless, they have different approaches and scoping for REDD+. The results from this study indicate that developed countries contribute to building a global regime on REDD+ with different strategies based on their interests and perspectives. These can be elucidated as leadership in forming the REDD+ regime. Analysis on activities to support REDD+ as international cooperation strategies by developed countries will help the dynamics of a global regime of REDD+ to be understood.